Aplicação de conjugado de microesferas de poliestireno para preparo de RNA no diagnóstico da cinomose canina por RT-qPCR - Tozato, Claudia de Camargo [UNESP] (2014)
The diagnosis of canine distemper is usually based on clinical suspicion of the disease. However, due to the different clinical forms of the disease and other disorders common to clinical signs, the laboratory diagnosis is necessary. The RT-PCR followed by NESTED is currently the method used to diagnosis of CDV (Canine Distemper Virus). The Chapter 2 aimed to standardized the technique of One-Step RT-qPCR-using Syber Green I system. Three commercial kits (Sigma®, Promega® and Qiagen®) were tested and compared. Analytical sensitivity of two detection systems (System A and System B) was determined using a standard curve. The three commercial kits tested detected the virus in 100% of samples from symptomatic dogs and the kit of Qiagen® showed better results. The System A detected approximately 10 RNA copies/μL and System B detected approximately 100 RNA copies/ μL in RT-qPCR and 10 RNA copies/ μL when followed by NESTED-qPCR. In Chapter 3 three immunoconjugates were developed with polystyrene microspheres (PM) using polyclonal hyperimmune anti-CDV antibody (IgY, IgG and protein A+IgG) to prepare RNA to canine distemper molecular diagnosis and comparison with the conventional method of RNA extraction by commercial kit. Conjugates were standardized and the analytical sensitivity was determined by standard curve. The diagnostic sensitivity was determined using IgY-conjugated, PM without conjugated antibodies and urine adsorption directly qPCR in tubes